Animal Ethics and the Philosophy of Its Existence; An Outline of the Theory of “Common Beliefs” - Mohsen Shiravand; Sepideh Razi (Al-Jami'ah: Journal of Islamic Studies, 2021)
Countless scientific efforts have been made for tackling the environmental crises and a relative success is achieved in awakening of different nations as regards the seriousness of the ever-increasing crisis. The current essay is also an effort in the same spirit. The goal of this essay is providing an outline of the Theory of “Common Beliefs”. This essay proves that animals like humans have such common beliefs as monotheism, prophecy and resurrection. Moreover, due to the difficulty of the acceptance of this idea for the mainstream minds, the possibility of the existence of such a claim is demonstrated based on the philosophical principles of Mulla Sadra. The method used in this research is documented-analytical using library sources. The main source of this study is Holy Quran, the exegeses of Quran, Islamic traditions as well as the works of Sadra and his followers. Among the results of the present research are making this claim acceptable in view of the rational and philosophical principles, creation of a spiritual, peaceful, and even humane sense in the domain of environment, establishment of an environmental law based on a generous interaction between the man and the animal and arrangement of the interreligious dialogues among the religiously grounded cultures. [tak terhitung usaha ilmiah dalam menghadapi krisis lingkungan dan cukup banyak keberhasilan yang dicapai dalam kebangkitan beberapa negara serius merespon pertambahan krisis. Dengan semangat yang sama, artikel ini ingin menyajikan outline teori Common Belief yang membuktikan bahwa binatang seperti halnya manusia menerima prinsip monoteisme, takdir dan kebangkitan kembali. Mengingat kesulitan penerimaan ide ini bagi orang awam, kemungkinan eksistensi klaimnya dapat ditunjukkan berdasarkan prinsip filosofisnya Mulla Sadra. Artikel ini menggunakan metode analisis dokumen dengan sumber utamanya adalah Qur’an, tafsir Qur’an, karya Mulla Sadra dan murid-muridnya. Beberapa kesimpulan menunjukkan bahwa klaim bisa diterima secara rasional dan filosofis, penciptaan spiritualitas, kedamaian, masuk akal dalam konteks lingkungan, dan kemapanan hukum lingkungan berdasarkan hubungan baik antara manusia dan mahluk hidup (binatang) serta mengatur dialog lintas keyakinan dengan latar budaya masing-masing].